Bupleurum marginatum Wall.ex DC in Liver Fibrosis: Pharmacological Evaluation, Differential Proteomics, and Network Pharmacology - Liu, Xiujie; Shi, Yu; Hu, Yinghui; Luo, Ke; Guo, Ying; Meng, Weiwei; Deng, Yulin; Dai, Rongji (Frontiers in Pharmacology, 2018)
Liver fibrosis is a common pathological feature of many chronic liver diseases. Bupleurum marginatum Wall.ex DC (ZYCH) is a promising therapeutic for liver fibrosis. In this study, 25 compounds were isolated from ZYCH, and the effects of ZYCH on DMN-induced liver fibrosis in rats were evaluated. The optimal effect group (H-ZYCH group) was selected for further proteomic analysis, and 282 proteins were altered in comparison to the DMN model group (FC > 1.2 or < 0.83, p < 0.05). Based on GO annotation analysis, clusters of drug metabolism, oxidative stress, biomolecular synthesis and metabolism, positive regulation of cell growth, extracellular matrix deposition and focal adhesion were signiﬁcantly regulated. Then networks of the altered proteins and compounds was generated by Cytoscape. Importantly, triterpenoid saponins and lignans had possessed high libdock scores, numerous targets, important network positions and strong inhibitory activity. These findings may suggest that triterpenoid saponins and lignans are important active compounds of ZYCH in liver fibrosis and targeted by proteins involved in liver fibrosis. The combination of network pharmacology with proteomic analysis may provide a forceful tool for exploring the effect mechanism of TCM and identifying bioactive ingredients and their targets.